Charles Péguy vu par Geoffrey Hill - Josette Leray (Revue LISA)
Geoffrey Hill’s long poem The Mystery of the Charity of Charles Péguy is a meditation on the French poet Charles Péguy, on the values he embodied and their relationship to the world he lived in and to History in general. Hill has a dual approach: he demonstrates a ruthless clarity throwing light on a historical reality that denies the values Péguy advocated, while appreciating Péguy’s spiritual greatness. Hill feels drawn towards his idealism but he acknowledges its dangers and uses an ironic distance to counterbalance it. He investigates the concept of heroism and at the same time that of innocence, an innocence which is aware of tragedy. This celebration of innocence is but short-lived, for the ideal is soon corrupted and appropriated by History, and becomes a dead letter. In the end Péguy will not pass a message and his “Charity” remains a mystery, but his poetry is his legacy. Péguy’s influence on poets and on Hill himself is what Hill’s poem ultimately celebrates.